Comparing PI3K/Akt Inhibitors Used in Ovarian Cancer Treatment - Wu, Yi-Hui; Huang, Yu-Fang; Chen, Chien-Chin; Huang, Chia-Yen; Chou, Cheng-Yang (Frontiers in Pharmacology, 2020)
Epithelial ovarian carcinoma is the most lethal gynecological malignancy. Herein, we sought to determine the efficacy of PI3K/Akt inhibition using three AZD compounds in a NOD-SCID xenograft mouse model and Akt regulation in a panel of eight ovarian cancer cell lines. Elevated Akt phosphorylation on Ser473 but not on Thr308 in cancerous tissues correlated with short progression-free survival, overall survival, and death. AZD8835 and AZD8186 inhibited Akt phosphorylation while AZD5363 augmented its phosphorylation on Ser473. To add, all compounds inhibited the Akt downstream effectors 4E-BP1 and p70S6 kinase. AZD8835 and AZD5363 sensitized chemoresistant ovarian cancer cells to cisplatin and paclitaxel treatment. Only AZD5363 could inhibit COL11A1 mRNA and promoter activity, which are important factors in Akt regulation and chemoresistance in ovarian cancer. By using a mouse xenograft model, AZD8835 and AZD5363, but not AZD8186, caused a significant reduction in tumor formation. AZD compounds did not change the mRNA expression of BRCA1/BRCA in ovarian cancer cells, but AZD8835 inhibited BRCA1/BRCA2 mRNA expression and p-ERK protein expression in OVCAR-8 cells with the KRAS mutation. This study highlights the importance of PI3K/Akt in ovarian tumor progression and chemoresistance and the potential application of AZD compounds, especially AZD8835 and AZD5363, as therapeutic agents for the treatment of ovarian cancer.